Dampak Kehilangan atau Pencurian barang yang Dibeli dengan Kredit pada Pembayaran Cicilan - Inayah Maulia (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This article discusses the legal implications concerning the loss or theft of goods purchased on credit in installment payments. The main focus of this article is to analyze the legal consequences that buyers may face when goods purchased under a credit scheme experience loss or theft. The discussion involves aspects such as buyer responsibility, the role of the seller or financing institution, and legal protections available to the buyer in such situations. The research method employed is legal analysis, detailing provisions of credit contracts, consumer protection regulations, and relevant court decisions. The research findings highlight the importance of understanding the rights and obligations of buyers in the context of the loss or theft of goods purchased on credit. Legal implications on installment payments also take center stage in outlining the potential impacts on the parties involved in such credit agreements..